Optimalisasi Penerapan Kurikulum Berbasis Kompetensi di Sanggar Tari Lintang Patria Kabupaten Blitar: Studi Implementasi Dana Evaluasi - Widowati Asmaraningwulan Purbaningrum; Anik Juwariyah; Welly Suryandoko (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
This study examines the implementation of the Competency-Based Curriculum (CBC) at Sanggar Tari Lintang Patria in Blitar Regency as an effort to develop technical skills and cultural understanding in the field of traditional dance arts. The curriculum is designed to integrate dance techniques with local cultural values, thereby producing a younger generation with strong artistic skills and cultural identity. The study uses a descriptive qualitative approach with observation, interviews, and documentation methods to explore the planning, implementation, and evaluation of the curriculum. The findings show that the implementation of CBC in the studio has made significant progress in mastering dance techniques, artistic expression, and cultural understanding. However, challenges faced include the need to adapt the curriculum to the times without losing its traditional essence. Internal and external evaluations indicate that the curriculum is quite effective, although there is a need to introduce contemporary dance and variations in teaching methods. The study also suggests the development of a more varied curriculum to accommodate the evolution of the arts and the broader needs of society. These findings are expected to contribute to the development of dance curricula in other non-formal art studios in the effort to preserve local culture and meet the demands of the ever-evolving art world.